Capacitive and resistive electric transfer therapy in rehabilitation: a systematic review. Issue 4 (December 2020) - Beltrame, Raffaello; Ronconi, Gianpaolo; Ferrara, Paola Emilia; Salgovic, Ludovit; Vercelli, Stefano; Solaro, Claudio; Ferriero, Giorgio
Abstract : Capacitive and resistive electric transfer (CRET) therapy is a physical treatment modality commonly used to treat musculoskeletal pain. It normally uses a longwave radiofrequency of 0.5 MHz. The system consists of a neutral plate and two different electrodes that can transfer energy in two modalities: capacitive and resistive. The aim of this systematic review was to identify and summarize the available data in the literature on this physical modality. From a search of articles published before December 2019 in MEDLINE and Scopus indexed journals, we retrieved 276 articles, 13 of which met the inclusion criteria for this review. Most articles dealt with musculoskeletal disorders, mainly spine disorders and knee osteoarthritis. More than 75% of the studies used a similar range of frequency (440–600 KHz). Almost all described an improvement in strength and function and reduced pain intensity after the treatment. Although nine of the 13 studies (70%) were randomized controlled trials, only two had a low risk of bias according to the Cochrane library assessment tool. CRET seems to be an effective therapy to decrease pain, and improve the quality of life and disability of patients affected by musculoskeletal disorders. There is no study on symptoms of patients with neurological disorders. Further research is necessary to standardize the therapeutic protocols across different orthopedic diseases, and to assess the benefits of CRET in other fields such as neurological or rheumatologic disorders.